Convalescent Plasma in the Treatment of Severe COVID-19: A Systematic Review and Meta-Analysis - Xuanguo ZHANG; Li XI; Fang PANG; Yan DU; Qiuzhen YUAN; Minjuan SHI; Jiping LIU; Hui MA; Bo LI (Tehran University of Medical Sciences, 2020)
Background: COVID-19 is a public health emergency of international concern. Its incidence rates and mortality are very high; however, so far, an effective drug treatment remains unknown. Based on the role of convalescent plasma therapy in previously identified viral pneumonias, patients with severe COVID-19 have been given this therapy. This systematic review and meta-analysis aimed to summarize the clinical evidence regarding the efficacy and safety of convalescent plasma therapy in the treatment of severe COVID-19. Methods: PubMed, Embase, Ovid, China Knowledge Network, China Biomedical, VIP Chinese Sci-tech Journal, Wanfang Database, and the International Clinical Trials Registry Platform were searched up to 21 June 2020, to identify clinical studies and registered trials on the use of convalescent plasma in the treatment of critically ill patients with COVID-19. Stata 13.0 was used to perform Meta-analysis. All records were screened as per the protocol eligibility criteria. Results: Nineteen clinical reports regarding convalescent plasma in the treatment of severe COVID-19 were included. Through systematic analysis, convalescent plasma was found to yield some efficacy on severe COVID-19 and had almost no obvious adverse reactions. Conclusion: Convalescent plasma therapy seems to yield some efficacy among patients with severe COVID-19 and almost no obvious adverse reactions were found. However, at present, the clinical evidence is insufficient, and there is an urgent need for support from high-quality clinical trial data.